A novel cascade approach to extract bioactive compounds from officinal herbs - Ding, Yubin; Morozova, Ksenia; Scampicchio, Matteo; Morini, Angelo; Ferrari, Massimiliano (Italian Journal of Food Science, 2022)
This research aims to compare a novel cascade extraction method with a conventional solid–liquid extraction method, both assisted by ultrasounds. The cascade extraction method consists of a sequential series of extractions performed with the same hydroalcoholic solvent, which is reused from one herb to the other. In practice, a hydroalcoholic solution is firstly used to extract one botanical herb. The resulting extract is then reused for the extraction of a second herb. The process is repeated as many times as the number of herbs composing the final formulation. The main advantage of this approach is firstly the lower need of solvents compared with the individual extraction procedures, where a fresh solvent is needed on each extraction step. Furthermore, extracts of the two methods (solid liquid vs cascade extraction) were characterized with several antioxidant assays (DPPH, ORAC, and FRAP) and total phenolic content (TPC). The results show that the solid–liquid extraction method achieves similar yields to total phenols and similar TAC in comparison to the extracts obtained by the cascade extraction method. Also, the HPLC analysis of the extracts showed that both methods lead to similar chromatographic profiles either when analyzed by an electrochemical detector (CoulArray) or by a spectrometric diode array detector (DAD). However, our findings support the idea that the cascade extraction method obtains extracts richer of minor peaks, showing a more complex bioactive profile. Such results could be explained considering that the solvent used during the series of cascade extractions was enriched not only by antioxidants but also by plant surfactants, like saponins, which increase the solvent solubility. Overall, this research shows that the cascade extraction method can not only provide officinal herb extracts with similar phenolic yield and antioxidant capacity than conventional solid–liquid extraction but also with a more complex bioactive profile compared to traditional solid–liquid extraction and with a minor consumption of solvents.